Geeks Win. - Ullman, Ellen (New York Times Book Review, 2001)
Reviews the book 'Go To: The Story of the Math Majors, Bridge Players, Engineers, Chess Wizards, Maverick Scientists and Iconoclasts--the Programmers Who Created the Software Revolution,' by Steve Lohr.